THU0184 TNF Production is Regulated by Adalimumab Treatment in Rheumatoid Arthritis Patients. (23rd January 2014) - Diaz-Torne, C.; Zamora, C.; Geli, C.; Diaz-Lopez, C.; Ortiz, M. A.; Moya, P.; Nieto, J. C.; Castellvi, I.; Cantó, E.; Casademont, J.; Juarez, C.; Llobet, J. M.; et al.
Abstract : Background: Adalimumab is a neutralizing anti-TNFα monoclonal antibody that blocks specifically TNFα action. It has been shown to be effective in clinical and quality of life improvement in rheumatoid arthritis (RA) patients. However, the influence of adalimumab on TNFα production and secretion remains unknown. Methods: Twelve rheumatoid arthritis patients with no previous biological therapy were treated with adalimumab according to clinical practice. We collected demographic (age and gender) clinical (disease duration and DAS28) and laboratory data (RF, a-CCP, ESR and CRP) before and 4, 12 and 24 weeks after the initiation of adalimumab. In whole blood stimulated with LPS, we evaluated: a) free secreted TNFα levels in supernatant (not neutralized by adalimumab) by ELISA; b) TNFα expression on monocyte surface (not neutralized by adalimumab) by flow cytometry; c) Intracellular TNFα production by flow cytometry. Results: Ten RA patients completed all time of treatment; two RA patients withdraw treatment due to adverse effects. Baseline characteristics of RA patients were: mean age 56.6 ± 12.6 years, 90 % were female, mean duration of disease was 13.7 ± 11.2 years, 70 % of RA patients were RF or anti-CCP positive, mean DAS28 5.05 ± 0.5, mean CRP was 15.6 ± 17.8 mg/L and mean ESR 40.1 ± 23.6 mm/h. Intracellular TNFa production was different in RA patients compared to controls (healthy donors) (33.15 ± 16.71 vs 71.28 ± 1.04% of CD14+TNFα+ cells respectively, p<0.05). After treatment with adalimumab, intracellular TNFα levels increased. Twenty-four weeks after initiating treatment, the intracellular TNFa levels in patients were comparable to controls. Levels of TNFα on monocyte surface were significantly reduced at four weeks and these levels remained low thereafter (see table). Significant changes in intracellular TNFα, surface TNFα and TNFα secretion were detected in RA patients with a good/moderate EULAR response to adalimumab. However, none of these changes were observed in RA patients with bad EULAR response. Conclusions: Active RA patients showed a defective regulation of TNFα production. Blocking TNFα with adalimumab corrected this defect. After receiving adalimumab, intracellular TNFa levels in RA patients and controls were comparable. Disclosure of Interest: None Declared